2022
DOI: 10.3389/fped.2022.897113
|View full text |Cite
|
Sign up to set email alerts
|

Tracing COVID-19 Source of Infection Among Health Personnel in a Pediatric Hospital

Abstract: Health personnel (HP) have been universally recognized as especially susceptible to COVID-19. In Mexico, our home country, HP has one of the highest death rates from the disease. From the beginning of the SARS-CoV-2 pandemic, an office for initial attention for HP and a call center were established at a COVID-19 national reference pediatric hospital, aimed at early detection of COVID-19 cases and stopping local transmission. The detection and call center implementation and operation, and tracing methodology ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The proportion of infected individuals varied by region: 73.6% in Eastern Europe, 59.5% in Central Europe, 21.4% in Western Europe, 30.9% in North America, and 25.1% in Southern Latin America ( 3 ). In addition, healthcare workers (HCWs) have been identified as particularly vulnerable with a higher risk of infection compared to the general population ( 4 ). An Italian study also reported that HCWs were more than twice as likely to be re-infected compared to non-HCWs ( 5 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of infected individuals varied by region: 73.6% in Eastern Europe, 59.5% in Central Europe, 21.4% in Western Europe, 30.9% in North America, and 25.1% in Southern Latin America ( 3 ). In addition, healthcare workers (HCWs) have been identified as particularly vulnerable with a higher risk of infection compared to the general population ( 4 ). An Italian study also reported that HCWs were more than twice as likely to be re-infected compared to non-HCWs ( 5 ).…”
mentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) emerged in December 2019 and rapidly spread across the globe (1-2). As of November 14, 2021, approximately 3.8 billion people had been infected or re-infected, accounting for 43.9% of the global population, with a peak in April 2021 (3). The proportion of infected individuals varied by region: 73.6% in Eastern Europe, 59.5% in Central Europe, 21.4% in Western Europe, 30.9% in North America, and 25.1% in Southern Latin America (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The epidemiological surveillance of all cases and contacts was carried out from April 2020 to November 2020. The tracing methodology within our hospital was published by de la Rosa-Zamboni et al ( 25 ).…”
Section: Methodsmentioning
confidence: 99%